Are contrast-enhanced and non-contrast MRI findings reflecting synovial inflammation in knee osteoarthritis: a meta-analysis of observational studies. Issue 2 (February 2020) - Shakoor, D.; Demehri, S.; Roemer, F.W.; Loeuille, D.; Felson, D.T.; Guermazi, A.
Summary: Objective: To determine the correlation between knee synovitis assessed on contrast-enhanced (CE) and non-contrast enhanced (NCE) magnetic resonance imaging (MRI) with histology in patients with knee osteoarthritis. Methods: A comprehensive literature search was performed, and related articles published through July 2018 were extracted. Spearman correlation coefficients of MRI-based scores with histology reports were pooled using random effects model. To evaluate presence of publication bias, Egger test was performed. Results: Of 2377 identified records, eight studies consisting of 246 MRI exams were included. Two studies reported results of dynamic CE (DCE)-MRI examinations (81 knees) and two studies reported results of NCE-MRI. There were moderate positive correlations between CE-MRI scores and macroscopic ( r  = 0.53 (95% Confidence Interval (CI):0.37–0.66), P  < 0.001) as well as microscopic ( r  = 0.56 (0.39–0.69), P  < 0.001) histology. DCE-MRI were strongly correlated ( r  = 0.71 (0.58–0.80), P -value<0.001), with microscopic histology reports, while the correlation for NCE-MRI was low positive ( r  = 0.44 (0.20–0.63), P  < 0.001). Meta-regression analysis showed that pooled correlation coefficients of DCE-MRI were significantly higher than CE-MRI (Slope = 0.29, SE = 0.13, P -value = 0.02). CE-MRI were also correlated with inflammatory infiltrate ( r  = 0.42), while the correlations for cell number of synovial lining ( r  = 0.27) and level of fibrosis ( r  = 0.29, P  < 0.001) were very low. Conclusion: Static and dynamic CE-MRI evaluation of knee synovitis were positively correlated with macroscopic and microscopic features of synovial membrane inflammation. Among the features of synovial tissue inflammation, CE-MRI scores correlated best with the inflammatory infiltrates of synovial tissue. Paucity of current evidence warrants further studies to assess performance of NCE-MRI on determining knee synovitis.